Elephants and habitats: the need for clear objectives - Lindsay, W. (Pachyderm, 1993)
In all places where elephants have been managed, the concerned authorities have expressed concern over elephant impact on vegetation and the risk of irreversible habitat change. On the other hand, management objectives have not been clearly defined, or if so their basis may not be entirely logical. Guidelines for management are discussed. The ecological processes which move the system from one state to another and the requirements of plant and animal species which are affected by the elephant-tree interaction are key aspects of the study.